CdO:Al films deposited by sol-gel process: a study on their structural and optical properties - Ilican, S.; Caglar, M.; Caglar, Y.; Yakuphanoglua, F. (Natl Inst Optoelectronics, 2009)
Undoped and Al-doped CdO films have been prepared by sol-gel spin-coating method. Effects of Al dopant on the structural and optical properties of CdO film have been investigated. The films were prepared for Al/Cd ratios of 1% and 3%. The crystal structure and orientation of the films have been investigated by X-ray diffraction method. CdO and CdO: Al films have polycrystalline structure with (111) preferential orientation. Al dopant increases the optical transparency of the films in the visible region. The optical absorption study reveals that the direct optical transitions occur in the optical band gap and the films have a direct optical band gap. The optical band gaps of undoped, 1% Al-doped and 3% Al-doped CdO films were found to be 2.476, 2.591 and 2.682 eV, respectively. The optical constants, refractive index, extinction coefficient and optical dielectric constants of these films were determined using transmittance and reflectance spectra. Al doping concentration affects strongly the optical constants of the thin films. The optical constants and optical absorption edge of the CdO thin film can be controlled by Al dopant.
Keywords: CdO; Sol-gel spin-coating; Optical band gap; Optical constant